A Research Agenda for Civil Society - Biekart, Kees (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Mapping a wide range of civil society research perspectives, this pioneering Research Agenda offers a rich and clear insight for academics and practitioners hoping to embark on future civil society research. Kees Biekart and Alan Fowler bring together over 20 expert contributions from researchers across the globe who are actively engaged in testing the old and generating new knowledge about civil society.